AN ANALYSIS OF THE EFFECTIVENESS OF AL-QARDH FINANCING ON MICRO BUSINESS DEVELOPMENT - Diana Nur Sena Wati; Finny Ligery; Agus Mushodiq (Jurnal Dinamika Ekonomi Syariah, 2026)
This study aims to analyze the effectiveness of Al-Qardh financing in supporting the development of micro-businesses. Al-Qardh is a non-interest benevolent loan intended to provide financial assistance for productive needs without commercial motives. Limited capital and insufficient financial knowledge often hinder small communities from expanding their businesses, making Al-Qardh a potential solution for empowering micro-enterprises. This research employs a qualitative field approach with data obtained through observation, interviews, and documentation. The informants include management, employees, and financing members of BMT Assyafi’iyah. The collected data were analyzed using an inductive thinking pattern to derive conclusions based on empirical findings. The results indicate that the implementation of Al-Qardh financing is generally effective in facilitating business growth. The financing procedure, eligibility assessment, disbursement mechanism, installment payment system, and monitoring process align with the concept of qardhul hasan as a loan provided without compensation, requiring borrowers to return the principal amount within the agreed period. Furthermore, Al-Qardh financing contributes to increasing business capital and encourages business continuity among members